DOES JOB SATISFACTION MATTER? ORGANIZATIONAL COMMITMENT OF ONLINE MOTORCYCLE DRIVERS IN BANDUNG INDONESIA - Romliansyah, Muhammad Alfidika; Hendrayana, Iqbal; Agustine, Riesta Adellya; Hakim, R. Fajri Ardhiah Nurul Gina Nul; Hasanah, Siti; Brahmana, Sunardi Sembiring (CENTRAL ASIA AND THE CAUCASUS, 2022)
Competition between companies engaged within the online motorcycle transportation sector is very high. This high competition certainly has an impact on the drivers. Higher competition can certainly weaken the organizational commitment of the drivers. The study is meant to investigate job satisfaction and organizational commitment relationship of online motorcycle drivers in Bandung, Indonesia. This research is explanatory research, namely research that appears at the connection between variables. The population of this research is all online drivers, and also the sample of this research is 114 motorcycle drivers. The results of hypothesis testing found that four dimensions of satisfaction: pay, promotion, co-workers, and nature of work had a positive and significant effect on drivers’ commitment, while the supervisory dimension had no effect on drivers’ commitment.